In Situ Measurement of Wind-Induced Pulse Response of Sound Barrier Based on High-Speed Imaging Technology. (20th September 2016) - Zhu, Chunli; Guo, Jie; Zhang, Dashan; Shen, Yuan; Liu, Dongcai
Abstract : The lifetime of the sound barrier is threatened by high-speed train-induced impulsive wind pressure as it passes by. The vibration response of the sound barrier during the process of train passing is difficult to be measured using conventional measurement methods because of the inconvenience of the installation of markers on the sound barrier. In this paper, the high-speed camera is used to record the whole process of the train passing by the sound barrier. Then, a displacement extraction algorithm based on the theory of Taylor expansion is proposed to obtain the vibration response curve. Compared with the result simulated by using the finite element method, the video extraction result shows the same head wave and tail wave phenomenon, demonstrating that the vibration measurement by using the high-speed imaging technology is an effective measuring way. It can achieve noncontact and remote vibration measurement and has important practical value.